2008
DOI: 10.1186/1472-6920-8-55
|View full text |Cite
|
Sign up to set email alerts
|

Self- and peer assessment may not be an accurate measure of PBL tutorial process

Abstract: BackgroundUniversidade Cidade de São Paulo adopted a problem-based learning (PBL) strategy as the predominant method for teaching and learning medicine. Self-, peer- and tutor marks of the educational process are taken into account as part of the final grade, which also includes assessment of content. This study compared the different perspectives (and grades) of evaluators during tutorials with first year medical students, from 2004 to 2007 (n = 349), from seven semesters.MethodsThe tutorial evaluation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 15 publications
5
31
0
11
Order By: Relevance
“…28 Clearly self-scoring, doesn't always discriminate low and high-achievers. use of self-assessment scores as final summative scores, could promote more generous self-scoring, 4 affecting productivity of PBL. Perhaps it would be useful for our students, to have this formative exercise mid-course, not end of course.…”
Section: Pbl Scores Compared To Pdq Scores For Low and Highachieversmentioning
confidence: 99%
See 3 more Smart Citations
“…28 Clearly self-scoring, doesn't always discriminate low and high-achievers. use of self-assessment scores as final summative scores, could promote more generous self-scoring, 4 affecting productivity of PBL. Perhaps it would be useful for our students, to have this formative exercise mid-course, not end of course.…”
Section: Pbl Scores Compared To Pdq Scores For Low and Highachieversmentioning
confidence: 99%
“…1,9 Machado showed that, self-assessment scores only correlated with peer-assessment scores, not tutor scores: concluding that students' scores are not useful for summative assessment, but should only be used for formative purposes. 4 In Das et al study, 75% of students, and 83% of tutors echoed that, students must be able to grade their work accurately, for their grades to be reliable. 1,9 Reports on Falchikov and Boud's study of 1989, showed correlations between self-assessment and teacher-assessments ranged from -0.05 to 0.82 (mean 0.39) and Gordon's study on health professionals, showed correlations between self-assessment and actual factual knowledge ranged from 0.02 to 0.65.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…High achieving students tend to under-rate themselves where-as low achieving students over-rate themselves in exercises where students have to rate their performance. [25][26][27][28][29][30] For quiz-responders, the mean scores were higher than non-responders in both the EOC-spotter and the PDQ. For the responders the correlation was higher between the quiz and free-response PDQ than between quiz and spotter (MCQ).…”
mentioning
confidence: 99%